Policy pathways for renewable and sustainable energy utilisation in rural coastline communities in the Niger Delta zone of Nigeria - E. O. Diemuodeke; T. A. Briggs (Energy Reports, 2018)
This paper presents the major barriers to sustainable rural electrification in the Niger Delta zone and suggests practicable policy pathways to tackle the barriers to the aggressive utilisation of renewable energy technologies in the Niger Delta zone. The barrier to the penetration of renewable energy technologies in the Niger Delta zone can be grouped into policy and institutional, technical, data and information gathering, socio-cultural and behavioural, economic and financial, political and market barrier, and inadequate decision space. The suggested policy pathways are driven from both the energy access and affordability considerations. Potential stakeholders, as the key drivers of the policy pathways, are identified with their various attributes and roles. It is shown that both positive energy policies of the Federal Government of Nigeria towards renewable energy penetration and the support from the oil producing and allied companies towards their operational areas would see the aggressive adoption and assimilation of the renewable energy technologies to meet the energy needs of the Niger Delta zone. This comprehensive paper will serve as a reference for policy players in the quest to address the energy problems in the coastal communities. It is anticipated that policy briefs, directed at the relevant stakeholders, would be crafted in deeper fashion to identify various actors and teasing what can be done in the sustainable energy space.
Keywords: 330; Sustainable energy; Energy-barrier; Niger Delta zone; Policy pathways; Rural coastline communities